Gender and age peculiarities of content changes of protein C, von Willebrand factor, vascular cell adhesion molecules sVCAM-1 in patients with acute left ventricle Q-wave myocardial infarction - S. M. Kyselov (Zaporožskij Medicinskij Žurnal)
Markers of hemostasis have an influence on the state of postinfarction remodeling processes.